Kurdish life and role in the Ottoman administration in Evliya Celebi's Sehayatname - Ahmed, Bzhar Othman (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2020)
Kurdistan was an important economic, political, and cultural territory of the Ottoman Empire. Many Ottoman-era scholars researched the region, mainly based on formal documents like Tahrir notebooks. Among the most important resources are travellers' narrations about the region, including those associated with Western missionaries and espionage activities. Ottoman officials and citizens travelled to Kurdistan for official duties and ethnographic travel itself, including Evliya Çelebi (the 17th century Ottoman traveller). He described the culture, civilization, and administration of Kurdistan in great detail for the fourth volume of his book of travel (Seyahatname). Çelebi visited almost all regions in Kurdistan between 1655 and 1656. In his visit to these places, Çelebi paid attention to history, science, administration and religious life. He narrated important information about mosques, palaces, hammams (public bath), madrasahs, and the antiquities of the region. He paid special attention to the history of administration and structure by giving specific details of information about ruling families in Kurdistan. He met with the rulers of that period and explained the structure of their administration. Also, he provided information about relations between the Ottoman Empire and local rulers. He examined and noted daily lives, religions, languages, foods, special days, social and cultural lives. The purpose of this work is to draw a critical analysis of Çelebi's Seyahatname, based on extensive archival resources and secondary sources to present a pioneering insight into the Ottoman engagement with Kurdistan during this period. In doing this, the researcher tries to present a more transparent overview of an important region that was to some extent neglected in Islamic historical studies. In this study, a Qualitative historical and textual analysis method was used. The most notable findings of this study are; Firstly, Çelebi visited Erzurum province (in south eastern Turkey) many years earlier than his travels to Kurdistan and provided invaluable data on Kurds living there at the time which has not been mentioned by other travellers. Secondly, he made an interesting remark about peace and harmony among various religious communities in Kurdistan. Thirdly, Çelebi made a unique contribution to the study of Islamic education and sciences by uncovering in great detail numerous madrasahs and other institutions of learning.